(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2025)
This study explores cutting-edge olive tree watering and fertilisation methods to improve olive production. The historical context highlights olive cultivation’s importance and the need for change. The symbiotic relationship between irrigation and fertilisation is carefully examined in our research of traditional practices and their development. We concentrate on drip irrigation and sprinkler systems to study improved irrigation methods. Rainwater collection and smart irrigation technology alter resource management. Our study of fertilisation strategies highlights controlled-release fertilisers, organic practices, and precision technology, which all have a role in nutrient delivery and absorption efficiency. This study uses actual data and theoretical frameworks to show how harmonising irrigation and fertilisation might boost economic viability and environmental stewardship. As issues arise, we negotiate technological subtleties, economic concerns, and ecological sustainability to advance innovation, informed legislation, and sustainable olive agriculture.